Hubungan Antara Motivasi Belanja Terhadap Kepuasan Konsumen Pada Konsumen CV. Tambak Ikan Lele Buyung Palembang (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the significant relationship between shopping motivation and customer satisfaction of customers of CV. Tambak Ikan Lele Buyung Palembang. The background of the study is based on the phenomenon of a significant decrease in the number of consumers, from an average of 130 people per month (2022) to 95 people (mid-2024), which indicates a problem of satisfaction related to service, order response, and delivery timeliness. This study uses a quantitative correlational method with a consumer psychology approach. The study population is consumers of CV. Tambak Ikan Lele Buyung, with a total of 110 respondents, and data collection was carried out using a Likert-scale questionnaire. Data analysis used a simple linear regression technique to test the hypothesis. The results of the study show that there is a very significant and positive relationship between Shopping Motivation and Consumer Satisfaction (r = 0.348, p = 0.000 < 0.01). This finding proves that the higher the consumer's shopping motivation, the higher the level of satisfaction they feel towards the shopping experience at the CV. Statistically, Shopping Motivation contributes 12.1% to the variation in Consumer Satisfaction, with the remainder influenced by other factors. This result is consistent with Self-Determination Theory (SDT), which asserts that fulfilling consumers' basic psychological needs (autonomy, competence, relatedness) during shopping activities is crucial in shaping customer satisfaction and loyalty. Practical implications: Companies are advised to improve service quality and interpersonal interactions to strengthen consumers' intrinsic shopping motivation.